Aplikasi Pembelajaran dan Panduan Fiber To The Home (FTTH) PT. Telkom Indonesia Berbasis Android - Muhammad Sukri Al Amin; Nelmiawati Nelmiawati (Politeknik Negeri Batam, 2020)
Learning Application and Guide Fiber To The Home (FTTH) of PT. Telkom Indonesia based on Android This final project discuss about design and manufacture of the FTTH (Fiber To The Home) Learning Application and Design Guide for PT Telkom Indonesia's new technicians. The initial problem so that the emergence of this idea is that there is no specific platform at PT. Telkom Indonesia that discusses FTTH in detail that is easily accessible and carried everywhere by a new technician from PT Telkom Indonesia. Therefore, the idea arose to design a learning media as well as an FTTH guide on an Android-based basis to make it easier for PT. Telkom Indonesia's new technicians as learning media and as a guide in completing work in the PT. Telkom Indonesia area. This research uses the MDLC method or Multimedia Development Life Cycle (Luther Sutopo, 2003) in the manufacturing process. Then the application made by Adobe Flash CS6 software. With this application, it will easier for new PT. Telkom Indonesia technicians to learn and know what FTTH is so that they can do work as technicians in PT Telkom Indonesia's area effectively.